Contractual liability - RUDĂREANU, Mariana (Annals of Spiru Haret University. Economic Series, 2010)
Any obligation entitles the creditor to claim the debtor to fulfil accordingly the performance he is bound to. An improper or delayed performance or the failure to perform by one party causes the other a prejudice, therefore entitling the latter to claim the former damages equivalent to the prejudice suffered.